Quality of life and psychomotor profile of children with attention deficit hyperactivity disorder (ADHD) - Juliana Barbosa Goulardins; Juliana Cristina Fernandes Bilhar Marques; Erasmo Barbante Casella (Arquivos de Neuro-Psiquiatria, 2011)
The knowledge of psychomotor development of children with attention deficit hyperactivity disorder (ADHD) may help in defining therapeutic approaches in order to minimize losses in their quality of life. The study objectives were to evaluate the quality of life and psychomotor profile of children with ADHD and check your correlation. Fourteen children, from seven to ten years, with ADHD combined type were evaluate using the scales PedsQL™ and Motor Development Scale. Results showed adverse effects of ADHD on quality of life and a deficit in motor skills. Nine participants (64.2%) were classified in motor development as "Normal Medium", followed by the classification "Normal Low" in four (28.5%) and "Low" in one subject (7.1%). We observed a positive correlation between quality of life and psychomotor development of children with ADHD, especially in areas: fine motor and spatial organization with social and psychosocial aspects, gross motor control with the emotional and temporal organization with the emotional, psychosocial and overall quality of life.